The nature of social support in an intergenerational ilonggo family in a fishing community - Alonday, Cheska Ariane
Nuclear family has been the common type of family in the society in the past but as time passed by, different forms of family emerged as well as family structure and the dynamics of the family have been changing. This study focused on the nature of social support in an intergenerational Ilonggo family specifically in fishing community. It discussed the different types of support, such as financial, emotional, and instrumental, exchanged among the family members and illustrated each patterns of support through the use of sociometry for the analysis of data gathered. This study also aimed to know whether there is a connection between the degrees of interaction to the social support exchanged. An intergenerational family household was purposively selected in Miag-ao, Iloilo which served as a case study. Each family member was asked to evaluate other family members individually through questionnaires. The results showed that the norms and the gender roles play an important part in the exchange of social support of the Filipino family members including their role obligations as well as the degree of interaction do not dictate the support given and received by the family members.